2014
DOI: 10.1093/infdis/jiu361
|View full text |Cite
|
Sign up to set email alerts
|

High Serum Levels of Norovirus Genotype-Specific Blocking Antibodies Correlate With Protection From Infection in Children

Abstract: High preexisting norovirus genotype-specific serum IgG titers and blocking activity in children indicate protection from norovirus infection in a strain-specific manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
78
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 43 publications
5
78
0
Order By: Relevance
“…Altogether, the results of this study indicate that measurement of the NoV strain-specific IgG level or the cross-reactive binding antibodies induced by immunization with different NoV VLPs alone is not adequate to determine the quality of immune responses (31,51). This is in line with our results obtained with human serum (30), where genogroup-specific cross-reactive IgG titers were raised after natural NoV infection but no equivalent blocking antibody titer increase was induced.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Altogether, the results of this study indicate that measurement of the NoV strain-specific IgG level or the cross-reactive binding antibodies induced by immunization with different NoV VLPs alone is not adequate to determine the quality of immune responses (31,51). This is in line with our results obtained with human serum (30), where genogroup-specific cross-reactive IgG titers were raised after natural NoV infection but no equivalent blocking antibody titer increase was induced.…”
Section: Discussionsupporting
confidence: 77%
“…GII.4 strain NoVs have an exceptionally broad HBGA binding repertoire and high transmissibility (2), explaining the predominance of GII.4 NoV infections worldwide (28). The quantity of genotype-specific antibodies that can block the binding of NoV VLP to the HBGA has been shown to increase remarkably after NoV infection or NoV VLP immunization in humans (18,19,29,30). Prechallenge levels of blocking antibodies in human serum have been shown to positively correlate with the protection of both NoV infection and illness, and it is generally accepted that especially blocking antibodies in serum play a substantive role in protection from NoV infection (18,31).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, patients with high serum IgG levels may be especially sensitive to antibiotics. Malm et al reported that patients with a high serum IgG titer can block norovirus infections [13] . Additionally, the effects of vaccination are assessed using serum IgG levels in various infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…58 The same group reported the generation of anti-GII.4 antibodies following infection among children less than 2 y old targeting closely related genotypes. 59,60 More than 90% of individuals are seropositive to NoV by the time they reach adulthood; however, the role of pre-existing immunity is still not fully understood when related to protection or reducing the risk of acquiring new NoV infections. 15 The fact that asymptomatic infection occurs at an early age as reported by outbreak and human challenge studies 48,[61][62][63] provides critical insight to the potential reservoir of transmission at an early age and its clear implication on the need for an effective vaccine.…”
Section: Viral Shedding Natural Infection With Nov and Seroprotectionmentioning
confidence: 99%